Effect of Hydrotherapy on Muscle Activities and Running Kinetics in Adult Males with Pronated Foot: A Randomized Clinical Trial - Mohammad Abdollahpor Darvishani; Mohsen Barghamadi; Amir Fatollahi (Pamukkale University, 2023)
The potential risk factor for injuries resulting from a pronated foot (PF) has been discussed. The water properties can be used to improve the biomechanics of the lower limb. Therefore, this study aimed to investigate hydrotherapy's effect on muscle activities and running kinetics in adult males with PF. This study was a randomized clinical trial type. Thirty adult males with PF were divided into two equally sized groups. Ground reaction forces (GRFs) were collected by a force plate on the runway. Muscle activities were recorded using a surface electromyography system. Statistical analysis was performed using repeated measures ANOVAs. The significance level was established at p